2021
DOI: 10.21037/apm-21-763
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of finerenone in patients with chronic kidney disease: a systematic review with meta-analysis and trial sequential analysis

Abstract: Background: The efficacy and safety of finerenone are unknown. Therefore, we performed this metaanalysis to investigate the efficacy and safety of finerenone in patients with chronic kidney disease (CKD).Methods: We systematically searched for relevant studies in the PubMed, Embase and Cochrane Library databases from database inception until December 2020. We selected randomized controlled trials assessing finerenone treatment in patients with CKD.Results: Four trials (n=7,048) met the inclusion criteria. Comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…The results of this meta-analysis found that finerenone, apararenone, and esaxerenone all can decrease the UACR in patients with CKD and T2D. This finding about finerenone is in line with a previous meta-analysis ( Fu et al, 2021 ). However, the esaxerenone subgroup showed significant statistical heterogeneity (I 2 = 85.6%), which may result from the different treatment durations (12 vs. 52 weeks).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results of this meta-analysis found that finerenone, apararenone, and esaxerenone all can decrease the UACR in patients with CKD and T2D. This finding about finerenone is in line with a previous meta-analysis ( Fu et al, 2021 ). However, the esaxerenone subgroup showed significant statistical heterogeneity (I 2 = 85.6%), which may result from the different treatment durations (12 vs. 52 weeks).…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that the use of non-steroidal MRAs (finerenone and esaxerenone) in patients with CKD and T2D may lead to decreased eGFR. In contrast, the previous meta-analysis showed that finerenone did not significantly decrease the eGFR in patients with CKD ( Fu et al, 2021 ). We found that there was significant heterogeneity (I 2 = 86%) among the included studies, and a significant difference was found in changes in eGFR between the finerenone group and the placebo group after excluding one study ( p = 0.01, I 2 = 0%) ( Fu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…As the third generation of the nonsteroidal mineralocorticoid receptor antagonist drug, finerenone demonstrates better protective effects on cardiorenal function compared with spironolactone or eplerenone due to the balanced tissue distribution into the heart and kidney [14-18], as well as a lower incidence of adverse events such as hyperkalemia [14]. In recent years, various research studies were conducted on the clinical effectiveness and safety of finerenone in cardiovascular and kidney diseases [19, 20]. Owing to a lack of relevant reviews reporting the efficacy and safety of finerenone on the renal function of DKD patients, this meta-analysis of randomized, placebo-controlled trials was conducted to evaluate the efficacy and safety of oral finerenone as a treatment for DKD.…”
Section: Introductionmentioning
confidence: 99%